Crystal structure of the lipopolysaccharide outer core galactosyltransferase WaaB involved in pathogenic bacterial invasion of host cells - Chen, Yatian; Gu, Jiayue; Ashworth, Gareth; Wang, Zhongshan; Zhang, Zhengyu; Dong, Changjiang (Frontiers in Microbiology, 2023)
Lipopolysaccharide (LPS) is essential for most gram-negative bacteria and plays an important role in serum resistance, pathogenesis, drug resistance, and protectionfrom harsh environments. The outer core oligosaccharide of LPS is involved in bacterial recognition and invasion of host cells. The D-galactosyltransferase WaaB is responsible for the addition of D-galactose to the outer core oligosaccharide of LPS, which is essential for Salmonella typhimurium invasion. Here we report the first crystal structures of WaaB and WaaB in complex with UDP to resolutions of 1.8 and 1.9 Ångström, respectively. Mutagenesis and enzyme activity assays confirmed that residues V186, K195, I216, W243, E276, and E269 of WaaB are essential for the binding and hydrolysis of UDP-galactose. The elucidation of the catalytic mechanism